Verbascum gimgimense (Scrophulariaceae), a new species from Muş province (Turkey) - Firat, Mehmet (Phytotaxa, 2017)
Verbascum gimgimense Fırat, a new species is described from Muş province, Turkey. From a morphological point of view, the new species appears to be similar to Verbascum leiocarpum, from which it differs in several morphological features including plant height, indumentum, leaf and flower size, filament hair colour, etc. A comprehensive description of the newly described species is provided, including detailed photographs, geographical distribution, habitat and ecology, vernacular name and IUCN conservation status.